Dynamic Behaviour of Coke Drums PSVs During Blocked Outlet Condition - Vakilalroayaei, Hessam (University of Waterloo, 2009)
The maximum yield taken in an oil refinery can not exceed 70% without including Delayed Coker Unit (DCU) as part of unit operations in the refinery. This implies naturally a big attraction on investing of such a unit for refiners. However, during the past decades, there were few refiners included Coker unit in the refinery, due to the fact of its large capital investment with a high marginal profitability. On the other hand the technologies developed to operate a coker unit, involve a series of process steps that require highly trained and well experienced operators with a state of art of design to overcome all the challenges with this unit operation. Safety, as a prime factor of design and operation requires much attention in the design of this unit. Among different safety consideration in the design and operation of Coker Unit, this project thesis focuses on the dynamic behaviour of Coke Drums PSV (Process Safety Valve) relief and its interaction with Blowdown section of the unit that leads also to the PSV relief of Blowdown section with change of temperature versus time during the first 15 minutes that is considered as the time required for operators intervention. The main findings in this thesis are about the complications in the design aspects of delayed coker unit as well as the importance and role of safety of operation of this unit. It also gave me an insight of cascade relief during the upset condition in an online coke drum and the importance of a reliable piping system to handle the hydraulics as well high temperature conditions.
Keywords: Dynamic Behaviour of Coke Drums; PSV Calculations of Coke Drums; Safety Considerations in Coke Drums Operations; Sequence of Operations of Coke Drums; Mode of Operations of Coke Drums; Chemical Engineering